On the unusually bright and frequent noctilucent clouds in summer 2019 above Northern Germany. (June 2021) - Gerding, Michael; Baumgarten, Gerd; Zecha, Marius; Lübken, Franz-Josef; Baumgarten, Kathrin; Latteck, Ralph
Abstract: Noctilucent Clouds (NLC) and Mesospheric Summer Echoes (MSE) are ice-related phenomena that occur occasionally in the mid-latitude summer mesopause region and more frequently in the polar regions. We observe both phenomena above our site at Kühlungsborn (Germany, 54.1°N, 11.8°E) by lidar and radar since 1997 and 1998, respectively. The NLC season 2019 turned out to be record-breaking with respect to different parameters. We observed the brightest NLC (backscatter coefficient at 532 nm of β max ≈ 54 ⋅ 10 − 10 m - 1 s r - 1 ), the longest continuous NLC ( 11 h) and the largest occurrence rates in June ( 20%). The seasonally averaged NLC height was found 600 m lower in altitude in 2019 compared to our long-term record. Consistent with the NLC data, radar observations of MSE showed unusually long-lasting echoes and a higher occurrence rate in June 2019. In contrast to our initial expectations, this increase of ice abundance in 2019 was not related to a generally stronger advection from higher latitudes. Mean winds observed by a nearby meteor radar were essentially weaker than in previous years, even though the winds were still typically southward during NLC. Instead, we found unusually low mean temperatures below 83 km altitude (and down to 75 km) being the main reason for these extraordinary observations. Furthermore, water vapor concentrations were slightly enhanced in June 2019. Low temperatures and enhanced water vapor may be caused by stronger upwelling in the upper mesosphere. However, there is no vertical wind data available. Low solar activity was also a factor that promoted these good NLC conditions. Overall, we judge this a singular event and not as an indicator for climate change. Temperature data in the mesopause region and below are taken from Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) on NASA's Thermosphere Ionosphere Mesosphere Energetics Dynamics (TIMED) satellite as well as Earth Observing System (EOS) Microwave Limb Sounder (MLS) onboard NASA's Aura satellite. Highlights: Unusual frequent and bright NLC/MSE observed in summer 2019 at Germany. Untypical conditions seem to be confined to about 2 weeks in June 2019, July normal. Observations explained by unusual low temperatures at 80–83 km and low mesopause. Disturbed MLT conditions potentially related to more eastward gravity waves.